Impact of COVID-19 on Communication Patterns of Czech and Slovak Cosplayers - Jelínková, Anna Paulína; Trnka, Andrej (Communication Today, 2023)
Cosplay is a distinctive hobby of fans of popular culture texts such as comics, manga, anime, digital games and films. Members of the cosplay community are active participants affiliated with various fandoms and communities who produce their own costumes, props and make-ups. An important part of those specific fan and community groups are fan conventions and festivals, which have been cancelled or postponed due to the COVID-19 pandemic situation. This fact is reflected significantly in usual behaviour, community life and participation of cosplayers. The main goal of this study is to identify the main changes and impact of the pandemic on Czech and Slovak cosplayers’ fan and community behaviour and communication habits. This study uses qualitative research strategy, specifically a series of in-depth interviews. The research unit consists of Slovak and Czech cosplayers who have been involved in this activity for at least eight years and are active members and participants in cosplay communities and fan conventions.